Action observation effects reflect the modular organization of the human motor system. (October 2017) - Hilt, Pauline M.; Bartoli, Eleonora; Ferrari, Elisabetta; Jacono, Marco; Fadiga, Luciano; D'Ausilio, Alessandro
Abstract: Action observation, similarly to action execution, facilitates the observer's motor system and Transcranial Magnetic Stimulation (TMS) has been instrumental in exploring the nature of these motor activities. However, contradictory findings question some of the fundamental assumptions regarding the neural computations run by the Action Observation Network (AON). To better understand this issue, we delivered TMS over the observers' motor cortex at two timings of two reaching-grasping actions (precision vs power grip) and we recorded Motor-Evoked Potentials (4 hand/arm muscles; MEPs). At the same time, we also recorded whole-hand TMS Evoked Kinematics (8 hand elevation angles; MEKs) that capture the global functional motor output, as opposed to the limited view offered by recording few muscles. By repeating the same protocol twice, and a third time after continuous theta burst stimulation (cTBS) over the motor cortex, we observe significant time-dependent grip-specific MEPs and MEKs modulations, that disappeared after cTBS. MEKs, differently from MEPs, exhibit a consistent significant modulation across pre-cTBS sessions. Beside clear methodological implications, the multidimensionality of MEKs opens a window on muscle synergies needed to overcome system redundancy. By providing better access to the AON computations, our results strengthen the idea that action observation shares key organizational similarities with action execution.